2022
DOI: 10.3389/fmed.2022.834663
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Biomechanics Differences Between Chinese and Caucasian Healthy Subjects

Abstract: PurposeThe aim of this study was to evaluate the difference between Caucasian and Chinese healthy subjects with regards to Corvis ST dynamic corneal response parameters (DCRs).MethodsTwo thousand eight hundred and eighty-nine healthy Caucasian and Chinese subjects were included in this multicenter retrospective study. Subsequently, Chinese eyes were matched to Caucasians by age, intraocular pressure (IOP), and Corneal Thickness (CCT) using a case-control matching algorithm. The DCRs assessed were Deformation A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…A recently published study has highlighted that biomechanical differences are demonstrated between White and Chinese eyes, and to the authors' knowledge, no previous study has investigated the sensitivity of biomechanical indices in detecting subclinical keratoconus in a South Pacific population where M aori and Pacific Peoples have a high prevalence of keratoconus. 18,19 The current study is in agreement with the previous studies investigating the TBI, finding an AUROC of 1.00 (95% CI = 0.99-1.00) for normal versus VAE-E corneas and an AUROC of 0.92 (95% CI = 0.86-0.98) when distinguishing between healthy and VAE-NT corneas. The TBI was not statistically superior to the CBI or the BAD-D in distinguishing between normal and VAE-E corneas, and this likely reflects that all 3 metrics are suitable for this purpose.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A recently published study has highlighted that biomechanical differences are demonstrated between White and Chinese eyes, and to the authors' knowledge, no previous study has investigated the sensitivity of biomechanical indices in detecting subclinical keratoconus in a South Pacific population where M aori and Pacific Peoples have a high prevalence of keratoconus. 18,19 The current study is in agreement with the previous studies investigating the TBI, finding an AUROC of 1.00 (95% CI = 0.99-1.00) for normal versus VAE-E corneas and an AUROC of 0.92 (95% CI = 0.86-0.98) when distinguishing between healthy and VAE-NT corneas. The TBI was not statistically superior to the CBI or the BAD-D in distinguishing between normal and VAE-E corneas, and this likely reflects that all 3 metrics are suitable for this purpose.…”
Section: Discussionsupporting
confidence: 92%
“…A recently published study has highlighted that biomechanical differences are demonstrated between White and Chinese eyes, and to the authors’ knowledge, no previous study has investigated the sensitivity of biomechanical indices in detecting subclinical keratoconus in a South Pacific population where Māori and Pacific Peoples have a high prevalence of keratoconus. 18,19…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated the good repeatability of SSI in eyes of different CCT and in myopic eyes ( Wang et al, 2021 ; Lu et al, 2022 ). However, SSI values may differ among races ( Chua et al, 2017 ; Vinciguerra et al, 2022 ). Liu et al reported that the SSI was relatively stable before 35 years of age and was positively correlated with anterior corneal curvature and IOP and negatively correlated with axial length (AL) in a healthy Chinese population ( Liu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, topical PG therapy reduced corneal stiffness, suggesting that the ocular hypotensive effect of these drugs is overestimated if we measure IOP with Goldman Applanation Tonometry (GAT) instead of bIOP. Because SSI can truly reflect the differences in material properties, one study ( Vinciguerra et al, 2022 ) evaluated the difference between Caucasian and healthy Chinese subjects in Corvis ST dynamic corneal response parameters and found a significant difference in SSI values.…”
Section: Discussionmentioning
confidence: 99%